Lubrication of Circumcision Site for Prevention of Meatal Stenosis in Children Younger Than 2 Years Old - Seyed Habibollah Mousavi-Bahar; Manoochehr Ghorbanpour; Hassan Bazmamoun (Urology Journal, 2008)
Introduction: Circumcision is one of the most common surgical operations throughout the world, and meatal stenosis is one its late complications. We evaluated the topical use of a lubricant jelly after circumcision in boys in order to reduce the risk of meatal stenosis. Materials and Methods: A randomized control trial was performed, in which 2 groups of boys younger the 2 years old underwent circumcision according to the sleeve method. The parents in the study group were instructed to use petroleum jelly on the circumcision site after each diaper change for 6 months. In the control group, no topical medication was used. The children were followed up regularly and evaluated for meatal stenosis, bleeding, infection, and recovery time. Results: A total of 197 boys in each group completed the study. None of the children in the study group but 13 (6.6%) in the control group developed meatal stenosis (P < .001). Infection of the circumcision site was seen in 3 (1.5%) and 23 (11.7%) children of the lubricant and control groups, respectively (P < .001), and bleeding was seen in 6 (3.0%) and 37 (18.8%), respectively (P < .001). The mean time of recovery in the lubricant group was 3.8 ± 1.2 days, while it was 6.9 ± 4.2 days in the control group (P = .03). Conclusion: Based on the findings of this study, it seems logical to use a lubricant jelly for reducing postcircumcision meatal stenosis and other complications.